Islamic Religious Education and the Challenges of Digital Anonymity: Fostering Students' Moral Development in the Era of Social Media - Siti Humairoh; Ikhwan Aziz Q; Eka Fitria Ningsih (Universitas Wahid Hasyim Semarang, 2026)
The rapid development of digital technology has transformed students’ communication patterns on social media. However, the weak reinforcement of digital ethics in education has created a reasoning gap, namely a discrepancy between freedom of expression and moral awareness, reflected in anonymous behavior without ethical consideration. This study aims to analyze the strategies of Islamic Education (PAI) teachers in addressing anonymous behavior among junior high school students. A qualitative case study design was employed at SMP Ma’arif 1 Metro. Participants included PAI teachers, the principal, and active social media users. Data were collected through in-depth interviews, observations, and documentation, then analyzed using Miles & Huberman’s interactive model. The findings indicate that although students actively use various platforms, negative interactions such as mockery, verbal abuse, and inappropriate comments leading to mild cyberbullying still occur. PAI teachers implement moral guidance, role modeling, integration of Islamic values (the concept of tabayyun), personal counseling, and collaboration with parents. The novelty of this study lies in its specific focus on students’ anonymous behavior on social media and the contextual integration of akhlakul karimah values into PAI teachers’ strategies—an underexplored area at the junior high school level. The contribution is an empirical understanding and a strategic model for teachers and schools in fostering Islamic-based digital ethics. The limitation is the single-school case study design, meaning the results cannot be generalized to all junior high schools with different characteristics.